Climate change impacts on biodiversity and ecosystems in Sri Lanka: a review - Jeevan Dananjaya Kottawa-Arachchi; Madawala Arachchillage Wijeratne (Nature Conservation Research: Заповедная наука, 2017)
The climate change impacts are felt by all facets and sectors of ecosystems, covering flora, fauna and environment. Sri Lanka is considered as a vulnerable, small island country that is under serious threat from climate change impacts. The most profound impacts of climate change in Sri Lanka will be on agriculture and food security, water and coastal resources, biodiversity changes, and human health. Sri Lanka's biodiversity is significantly important both on a regional and global scale as it has the highest species density for flowering plants, amphibians, reptiles, and mammals. Sri Lanka's varied ecosystems provide many services that are of significant economic value and play a crucial role in providing goods and ecosystem services. The subsequent sections featuring specific aspects of biodiversity in forests, freshwater wetlands, coastal and marine systems and agricultural systems, provide greater detail on the ecosystem services and bio-resources. Habitat loss and fragmentation, invasive alien species, deforestation and forest degradation, development projects, environmental pollutions and climate change (global warming) are the major threats to the biodiversity of the country. Climate change impacts on environment lead to a reduction in the distribution and abundance of species, especially endemics, which may even result in their global extinction. The introduction of various policies and guidelines in relation to environment is a good sign for conservation of ecosystems and biodiversity. The government of Sri Lanka has been implementing various environmental projects aiming at reducing deforestation and degradation of ecosystems. Policies and measures already developed under such initiatives will no doubt preserve natural habitats for plant and animal species. However, being a developing country with many economic challenges, the funds and expertise available for monitoring climate change impacts and biodiversity conservation are not sufficient.